LockyCloudCore - CTT locker management infrastructure - Seleiro, Miguel Moreira Lopes (2024)
Abstract The concept of Edge Computing came has a way to address the concerns related to the integration of Internet of Things (IoT) in a cloud service infrastructure, such as resource limitations, performance requirements, and data safety and privacy. For developers wanting to create a such an infrastructure, an analysis on how to perform this integration need to be made, from choosing which architecture to use in the system, to how it will be deployed, and how to optimize the data processing at the edge. Through the development of a management infrastructure for the CTT locker network, Locky, we demonstrate the factors that need to be taken into consideration when developing a distributed system with edge devices, as well as testing and comparing orchestration runtimes for edge devices.